Our Pride: Cloned Buffalo ‘Garima–II’ - Chauhan, M. S.; Manik, R. S.; Singla, S. K.; Singh, M. K.; Palta, P (Indian Farming, 2015)
Embroynic stem cells have the potential to develop into any type of cells which can be used for developmental and therapeutical studies. Scientists at NDRI, Karnal successfully developed a fully grown buffalo, Garima-II, from ES cells which has given birth to a normal calf, Mahima, in next generation.